2009
DOI: 10.3846/1648-0627.2009.10.150-158
|View full text |Cite
|
Sign up to set email alerts
|

Innovations at Workplace: An Evidence-Based Model for Safety Management

Abstract: Abstract. Safety culture is a sub-unit of organisational culture, which affects members' attitudes and behaviour in relation to organisation's ongoing health and safety performance. Many companies want to enhance their safety culture or some aspect of safety behaviour trying to find the effective way forward. Safety culture in small and medium-scale (SMEs) enterprises has received very little attention in Estonia. Estimates suggest that these enterprises have serious problems aggravated by limited access to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Existing models of Safety Culture are described and analyzed in depth in previous research [31]. Reviews of safety culture surveys identified some common aspects, for instance: management concern and commitment, personal responsibility, peer support for safety, employees' involvement in health and safety activities, and the SMS [4]; [21]; [24].…”
Section: Model Of Safety Culture and Knowledge Management Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing models of Safety Culture are described and analyzed in depth in previous research [31]. Reviews of safety culture surveys identified some common aspects, for instance: management concern and commitment, personal responsibility, peer support for safety, employees' involvement in health and safety activities, and the SMS [4]; [21]; [24].…”
Section: Model Of Safety Culture and Knowledge Management Aspectsmentioning
confidence: 99%
“…In order to fill this gap in the literature, based on previous empirical research and literature review, Järvis & Tint [31] proposed a new reciprocal safety culture model with a new construct -'communities of practice' -shared knowledge in order to reflect not only specific organizational (situational/ environmental), behavioral and psychological aspects of safety culture, but also include knowledge management aspects that incorporate both tacit and explicit safety knowledge and understanding. Thus, the concept of CoP is important in addressing not merely employees' behavior, practices and norms, but simultaneously the role of management within the organization in providing a facilitating and enabling climate of safety through which safety cultures can be embedded in organizational practice.…”
Section: Model Of Safety Culture and Knowledge Management Aspectsmentioning
confidence: 99%
“…The authors emphasize that the potency of the reciprocal model [24]; [25] for analyzing safety culture may be different in any given situation and might be influenced by potentially important internal and external organizational factors like environment, context, governance, relevant regulations, design etc. The reciprocal interactions among psychological, behavioral and organizational variables, which have been recognized and reflected in the major safety culture models, as well as the added knowledge variable indicate that the four dimensions to measure the overall safety culture of an organization are psychological, behavioral, organizational and knowledge aspects of safety culture.…”
Section: Safety Of Technogenic Environmentmentioning
confidence: 99%
“…The case studies were intended to promote a better understanding of the rationale of current safety culture in Estonian manufacturing SMEs. Results from qualitative studies [7]; [16]; [25]; [27] were used in order to complement and verify the results gained from the safety survey. The exploratory study was based on workplace visits, observations, audits and semistructured interviews with senior managers, as well as focus group interviews with workers.…”
Section: Safety Interviews Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation